Bezpieczeństwo handlu elektronicznego - Ciesielczyk, Teresa; Watras, Grażyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In this article we present some issues concerning security of e-commerce. In the first part we underline technological and organizational threats of this form of business activity. Ways of protection based on both legal and technological security were also discussed. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 68-74